Monopoly bingo sebagai media permainan untuk meningkatkan self efficacy pada siswa SMP - Alifa Mulzi, Rahma; Iswinarti (Universitas Muhammadiyah Malang, 2024)
Self-efficacy is a belief in the abilities possessed by each individual. Self-efficacy has an important meaning for every student that affects student success in completing their tasks. Therefore, each student has a different level of self-efficacy, therefore self-efficacy has an important role in students’ abilities. Students who have high self-efficacy are able to achieve the expected goals, while students who have low self-efficacy tend not to want to complete the tasks given by their teachers. This study aimed to determine the use of monopoly bingo games to increase self-efficacy in junior high school students. The research method used was quasi-experiment with two pretest-posttest control group design designs with data collection using the General Self Efficacy Scale as many as 10 items. The data analysis test used the Paired Sample T-test and the Independent Sample T-test and the results obtained that there was a significant influence on junior high school students, so that from the results of this study monopoly bingo provided an increase in self-efficacy in junior high school students.